Rediseño del proceso de producción de agua fría para la climatización del parque tecnológico Zonamérica (2021)
The main objective of this project is to establish the process of improvement in the production of water by condensation of the Zonamerica technology park, which is motivated by the need to alleviate the over-costs accrued by the inefficiency that today are generated in the consumption of electrical energy and drinking water, designing a possible solution to the problems associated with fluid concepts evidenced in the management and control software of the system.